2022
DOI: 10.3390/biomedicines10030728
|View full text |Cite
|
Sign up to set email alerts
|

Detection of TERT Promoter Mutations as a Prognostic Biomarker in Gliomas: Methodology, Prospects, and Advances

Abstract: This article reviews the existing approaches to determining the TERT promoter mutational status in patients with various tumoral diseases of the central nervous system. The operational characteristics of the most common methods and their transferability in medical practice for the selection or monitoring of personalized treatments based on the TERT status and other related molecular biomarkers in patients with the most common tumors, such as glioblastoma, oligodendroglioma, and astrocytoma, are compared. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 92 publications
4
18
0
Order By: Relevance
“…Thus, for instance, rs6265 (BDNF) only has an association in the “solos and depressed individuals” group and not in the solos group or in the depressed individuals group ( Table S4 available in Supplementary Materials ). Against the evolutionary models of loneliness, in which it is proposed that the presence of certain genetic variants would be responsible for a greater sensitivity to socioenvironmental factors and would lead to higher levels of loneliness [ 60 ], it seems that alleles of the SNPs related to changes in telomere length, such as those of SYT16 and BDNF, would play a more important role in the group of “solos and depressed individuals”. Several studies have demonstrated the association between depression and telomere shortening [ 138 , 139 ], although this association with the alleles of the SNP rs2487999 or rs12335203, identified among the solos group, is not confirmed in the group of “solos and depressed individuals”.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, for instance, rs6265 (BDNF) only has an association in the “solos and depressed individuals” group and not in the solos group or in the depressed individuals group ( Table S4 available in Supplementary Materials ). Against the evolutionary models of loneliness, in which it is proposed that the presence of certain genetic variants would be responsible for a greater sensitivity to socioenvironmental factors and would lead to higher levels of loneliness [ 60 ], it seems that alleles of the SNPs related to changes in telomere length, such as those of SYT16 and BDNF, would play a more important role in the group of “solos and depressed individuals”. Several studies have demonstrated the association between depression and telomere shortening [ 138 , 139 ], although this association with the alleles of the SNP rs2487999 or rs12335203, identified among the solos group, is not confirmed in the group of “solos and depressed individuals”.…”
Section: Discussionmentioning
confidence: 99%
“…The maintenance of telomere length is key since excessive shortening would lead to the appearance of symptoms associated with premature aging, and aberrant activity could favor the immortality of malignant cells. In recent years, there has been a number of publications on the search for mutations in the TER (RNA sequence of telomerase) sequence and in the TERT (telomerase reverse transcriptase) gene in various pathologies such as Zinsser–Cole–Engmann syndrome, also called Dyskeratosis Congenita [ 58 ]; aplastic anemia [ 59 ]; different types of cancer such as glioblastoma [ 60 ], melanoma [ 61 ], thyroid carcinoma [ 62 ], and breast cancer [ 63 ], among others; idiopathic pulmonary fibrosis [ 64 ]; and atherosclerosis [ 65 ] and more. Carroll et al (2013) [ 66 ] observed that elderly people (65–84 years), both men and women, with less social support had shorter telomeres.…”
Section: Introductionmentioning
confidence: 99%
“…Pathological diagnosis was made according to the 2021 (fifth edition) classification criteria for central nervous system brain tumors. IDH and TERT mutation statuses were obtained by next-generation sequencing, as described elsewhere (Arita, Narita, Takami et al, 2013;Hasanau et al, 2022). in a ratio of 7:3.…”
Section: Pathological Assessmentmentioning
confidence: 99%
“…TERT mutations occur mainly in the promoter region but rarely in the coding region [40,41], see Figure 3. Gene mutations of TERT promoter (TERTp) cause telomerase reactivation in approximately 90% of solid tumors.…”
Section: Tertmentioning
confidence: 99%